Exploring pianists' embodied concepts of piano timbre: An interview study. Issue 5 (19th October 2020) - Li, Shen; Timmers, Renee
Abstract : Whether piano touch can influence piano timbre or not is a highly contested topic between acousticians and musicians. To gain insight into the ways in which pianists understand and use timbre, eight piano students were interviewed about their conceptualisation of timbre and ways of producing different timbres on the piano. Results indicate that pianists interpret timbre holistically as the overall sonic outcome and use embodied conceptualisations to produce timbre: expected/intended timbral effects are associated with corporeal experiences and the body and mind are strongly coupled in perception and production.